Znamená samostatný útvar logistiky jiný důraz na spolehlivost, rychlost nebo náklady? - Koutný, Stanislav (Univerzita Pardubice, 2015)
In preparation for the broader topic structure of logistics processes was research done. The dissertation describes the design of parameters of the logistic processes structure in a manufacturing company. Structure of logistic processes in a manufacturing company means the logistic processes and their relationships in a manufacturing company. The research for the dissertation was mixed one (quantitative and half-structured qualitative research) and was conducted in 70 manufacturing enterprises in the Czech Republic. The research was conducted in South and Pilsen region in May 2013. The research focused on finding the relationship of certain characteristics of the company (and its production) on the one hand and decision for centralized structure for managing logistics processes in the company on the second hand. One of the research questions was, if the choice of an independent central logistics department in a manufacturing company is in relation with emphasis on reliability, speed or cost. The aim of this paper is to present some results of this research. The result is: the decision for centralized structure for managing logistics processes in the company tends to be related to the effort of high reliability.
Means a separate logistics department, other emphasis on reliability, speed or cost?
Keywords: logistics; logistics processes; logistics design; logistic structures; manufacturing; L22; L23